Environmental Preservation in the Islamic Perspective for the Quality of the Welfare of the People - Syafitri, Pangesti Diah Dewi; Jamil, Helmun (Indonesian Journal of Islamic Education and Local Culture, 2025)
In the view of Islam, environmental conservation is not only a duty of humans as stewards of the Earth but also a foundation for the community's overall welfare. This article elucidates how the concept of quality welfare for the community in Islam is closely related to environmental conservation, outlining several vital aspects. Firstly, the article highlights the relationship between environmental health and cleanliness with the physical welfare of the community, as well as the importance of sustainable resource management to support the community's economic needs. Second, it emphasizes the importance of maintaining the balance of natural ecosystems to prevent disasters and social conflicts. Thirdly, the article discusses the positive impact of environmental conservation on the spiritual welfare of the community, as reflected in the respect for nature as Allah's creation. Fourthly, it describes how environmental conservation efforts can enhance social awareness and strengthen community solidarity. Thus, the article concludes that environmental conservation in Islam is not only about preserving nature physically but also about creating holistic welfare for the community, encompassing physical, economic, spiritual, and social aspects.